Beyond words: Conceptual framework for the study and practice of hypnotherapeutic imagery. Issue 4 (1st April 2022) - Short, Dan
ABSTRACT: This paper provides a conceptual framework for the study and clinical application of hypnotherapeutic imagery (HTI). Using the grounded theory method of conceptual analysis, a unified theoretical framework is constructed from a multidisciplinary review of literature (i.e., this new theory is based on the collection and analysis of independently sourced data). The aim is to enumerate the chorographical features of HTI simulations within the mental landscape, rather than seeking to predict them. This is achieved using a combination of ontological, epistemological, and methodological inquires. Because mental simulation is both symptomatic of mental disorders and a psychotherapeutic agent, used across various treatment modalities, an attempt is made to isolate those variables that differentiate HTI from other instances of mental simulation. Lastly, applied principles from multiple disciplines are used to formulate HTI methodology designed to effectively enhance intuitive understanding and unconscious problem-solving.